Feasibility study on the replacement of copper conductors with copper-cladsteel conductors in photovoltaic plants - Minosso, Vinicius Maschio; Picolotto, Tiago Volnei; Reis Junior , Paulo; Cechin, Luana; Reis, Mari Aurora Favero (Latin American Journal of Energy Research, 2025)
This study examines the technical and economic feasibility of replacing copper conductors with copper-clad steel conductors in the grounding systems of a commercial-scale photovoltaic plant. A literature review was conducted to identify existing applications, followed by an analysis of data from a photovoltaic complex where copper grounding conductors and rods were replaced by copper-clad steel. Results show that the substitution is feasible, maintaining grounding efficiency within regulatory standards, despite higher electrical resistivity. The change also results in cost reduction, increased mechanical strength, and lower risk of material theft, factors that support sustainability and operational safety. Further research is recommended on long-term performance and durability in different soil conditions. The findings suggest that copper-clad steel conductors are a promising alternative for large-scale photovoltaic applications, contributing to sustainable and cost-effective energy solutions.
Keywords: Copper-clad steel conductor; sustainability; photovoltaic power plant; electrical conductivity.